Breast Milk Iodine and Iodine Status of Breast-Fed Infants (Delta Medical College Journal, 2015)
Background: Breast milk is the only source of iodine for exclusively breast-fed infants. Iodine status of breast-fed infants depends on iodine in breast milk and also number of feeding in 24 hours. Iodine deficiency and iodine excess both have bad impact on infants health.Objective: To measure the iodine in breast milk and to evaluate iodine status of their breast-fed infants.Materials and method: This observational analytical study was carried out in the department of Biochemistry, Bangabandhu Sheikh Mujib Medical University, Dhaka with active cooperation of Kumudini Womens Medical College Hospital, Mirzapur, Tangail involving fifty lactating mothers and their exclusively breast-fed infants. Early morning urine and breast milk samples were collected in dry and clean plastic container free from any chemical contamination. Urinary iodine was used as indicator for assessing iodine status. All statistical analyses were done by using SPSS (statistical programme for social science) 12 version software package for Windows.Results: The median (range) urinary iodine concentration of lactating mothers and their breast-fed infants were 225.25 ?g/L (61.50-530.00) and 225.75 ?g/L (100.50-526.00) respectively. The median (range) breast-milk iodine concentration was 157 ?g/L (54.50-431.50) which was more than three times of recommended minimum concentration (50 ?g/L). Only 2 (4%) lactating mothers had mild biochemical iodine deficiency (UIE, 50-99 ?g/L). There was no biochemical iodine deficiency of breast-fed infants. Iodine in breast milk of lactating mothers was positively correlated with their urinary iodine excretion (p